CircAGFG1 Promotes Osteosarcoma Progression and Stemness by Competing with miR-302a-3p to Upregulate the Expression of LATS2. (31st July 2022) - Li, Tongchun; Xing, Guangjie; Lu, Liangliang; Kong, Xiangzhen; Guo, Jinwei
Abstract : This study aimed to investigate the effect of circRNA (circAGFG1) on the proliferation, migration, invasion, and cell stemness of osteosarcoma cells by targeting miR-302a to regulate LATS2. The expression of circAGFG1 in osteosarcoma cells and normal osteoblasts was detected by real-time fluorescent quantitative PCR (RT-qPCR). Cell proliferation, clone formation, and invasion were detected by CCK-8, clone formation, and cell invasion assays. In vivo tumor formation assay was used to detect the effect of circAGFG1 on tumor growth. The expression level of circAGFG1 was upregulated in osteosarcoma cells. The downregulation of circAGFG1 inhibited the proliferation, invasion, and migration of osteosarcoma cells. The overexpression of circAGFG1 enhanced the stemness of osteosarcoma cells. CircAGFG1 was specifically bound to miR-302a to regulate the expression activity of miR-302a. MiR-302a specifically bound to the 3′UTR of LATS2 and inhibited the expression of LATS2. The overexpression of miR-302a reversed the effect of circAGFG1 on the proliferation, invasion, and migration of osteosarcoma cells. CircAGFG1 regulated the expression of LATS2 by miR-302a, thereby regulating the proliferation, migration, and invasion of osteosarcoma cells.